Conceptualising mobility - Matthias Deschryvere (The Research Institute of the Finnish Economy (ETLA), 2010)
The information on the impact of mobility on society is plenty but scattered. A good understanding of the impact of mobility requires first an understanding of what mobility actually means. This paper lists aspects of mobility that can contribute to a useful conceptualisation. It is found that in its core mobility is about connectivity of individuals. In addition mobility is more than just geographical mobility of human interactions. Mobility also has important temporal and contextual dimensions. Mobile technology has increased mobility in these dimensions and has been the driver of digitalising society into a mobile network society that connects not only individuals but also remote data and objects. There seems to be a need for an in depth conceptualisation of mobility that has to be updated along the lines of a fast moving mobile technology and mobile society
Keywords: L96; O30; 330; mobility; mobile communication; network society